KADAR KOLESTEROL DARAH PADA PENDERITA OBESITAS DI KELURAHAN KORPRI SAMBIROTO SEMARANG - Andri Sukeksi; Herlisa Anggraini (JURNAL KESEHATAN, 2009)
Abstract Patients with obesity have excessive fat accumulation in the body, causes the occurrence of obesity is usually caused by an abnormal eating pattern that is eaten in the number of very large and eat at night.. Obese People hove elevated levels of cholesterol in the body (hypercholesterolemia) (Mangku Sitepoe, l993). Cholesterol is a form of at that is naturally present in foods derived from animals, which allows the human body to make sex hormones and sexual function, adrenal hormones are necessary in the process of metabolism, and vitamin D. (lmam Suharto, 2004). Cholesterol is also useful for transporting fat in the blood throughout the body, which in a long time that blood vessels may be narrowed or closed. If the arteries (arteries) that provide blood to the hear, brain or organs - covered other important organs, can lead to risk of atherosclerosis, heart attack, stroke or failure of other vital organ functions. High levels of cholesterol called hypercholesterolemia is closely associated with the disease of obesity. (Corine T. Netzer, 1994). Based on the above background raised The question,